Transgenic Production of an Anti HIV Antibody in the Barley Endosperm. - Goetz Hensel; Doreen M Floss; Elsa Arcalis; Markus Sack; Stanislav Melnik; Friedrich Altmann; Twan Rutten; Jochen Kumlehn; Eva Stoger; Udo Conrad (PLoS ONE)
Barley is an attractive vehicle for producing recombinant protein, since it is a readily transformable diploid crop species in which doubled haploids can be routinely generated. High amounts of protein are naturally accumulated in the grain, but optimal endosperm-specific promoters have yet to be perfected. Here, the oat GLOBULIN1 promoter was combined with the legumin B4 (LeB4) signal peptide and the endoplasmic reticulum (ER) retention signal (SE)KDEL. Transgenic barley grain accumulated up to 1.2 g/kg dry weight of recombinant protein (GFP), deposited in small roundish compartments assumed to be ER-derived protein bodies. The molecular farming potential of the system was tested by generating doubled haploid transgenic lines engineered to synthesize the anti-HIV-1 monoclonal antibody 2G12 with up to 160 μg recombinant protein per g grain. The recombinant protein was deposited at the periphery of protein bodies in the form of a mixture of various N-glycans (notably those lacking terminal N-acetylglucosamine residues), consistent with their vacuolar localization. Inspection of protein-A purified antibodies using surface plasmon resonance spectroscopy showed that their equilibrium and kinetic rate constants were comparable to those associated with recombinant 2G12 synthesized in Chinese hamster ovary cells.